Poster No. 014 Diurnal and weekly variation in thrombotic and fibrinolytic status in healthy individuals. (21st October 2022) - Memtsas, Vassilios P; Gue, Ying X; Kanji, Rahim; Gorog, Diana A
Abstract: Background: Studies assessing individual enzymatic markers of fibrinolysis in healthy volunteers and patients with coronary artery disease indicate circadian variation. This is thought to be primarily attributable to changes in plasma plasminogen activator inhibitor-1 (PAI-1). It is unknown, whether elevated PAI-1 levels in plasma translate into a global impairment of fibrinolysis. Methods: A single centre, prospective, observational study was conducted in 50 healthy volunteers. Native, non-anticoagulated whole blood samples were obtained at two different time points on the same day, 8–12 hours apart. Furthermore, global thrombotic and fibrinolytic status over time was assessed by obtaining samples from 20 volunteers weekly, at the same time of day, for 4 weeks. The Global Thrombosis test was used to assess time taken to form an occlusive thrombus under high shear (occlusion time) and time taken for spontaneous restart of flow as a measure of endogenous fibrinolysis (lysis time). Results: There was no significant difference between the morning and evening thrombotic occlusion time (delta −25.6[ ± 100.7] sec, P = 0.079) or between the morning and evening endogenous fibrinolysis time (delta 82.5[IQR−272–307]sec, P = 0.397). Over the course of 4 weeks there was no statistically significant variation in occlusion time ( P = 0.542) or lysis time ( P = 0.562) between the different weekly visits within individuals. Conclusion: Assessment of global thrombotic and fibrinolytic function in whole blood does not appear to exhibit diurnal variation in healthy volunteers. These measurements appear to be stable over time, making this a potentially suitable method for assessing the thrombotic/fibrinolytic status of an individual over time.